The Ethics of Ikhtilaf in Islamic Law in Building Social Harmony within Muslim Communities - Nadia Aristia Mustari; Muh Rezky Afdal; M. Imam Khalis; Besse Ruhaya (Sekolah Tinggi Ilmu Tarbiyah Bustanul Ulum Lampung Tengah, 2026)
Ikhtilaf refers to differences of opinion among Islamic scholars in determining legal rulings on furu'iyyah (subsidiary) issues based on non-definitive evidence. As an integral part of Islamic intellectual tradition, ikhtilaf has shaped the development of Islamic jurisprudence since the era of the Prophet Muhammad’s Companions. Unlike previous studies that examine ikhtilaf from isolated perspectives, this study integrates its epistemological, ethical, and contemporary social dimensions while highlighting its relevance to Islamic education, character formation, and religious moderation. Using a library research method with a normative-historical approach, data were collected from the Qur’an, Hadith, classical Usul al-Fiqh, fiqh literature, and relevant scholarly works, then analyzed through content analysis. The findings reveal that ikhtilaf arises from differences in hadith transmission, socio-political contexts, legal reasoning, and legal sources. Understanding these causes promotes tolerance, discourages sectarian fanaticism, strengthens respect for scholarly ijtihad, and supports the integration of adab al-ikhtilaf into Islamic education to preserve Muslim unity.